PENGARUH KONSENTRASI DAN INTERVAL WAKTU PEMBERIAN BIOSAKA TERHADAP PERTUMBUHAN DAN PRODUKSI TANAMAN JAGUNG MANIS (Zea mays saccharata Strut) - Muh. Ali, Nur Hainul; Muhanniah, Muhanniah; Syarifuddin, Rifni Nikmat (Jurusan Budidaya Tanaman Perkebunan, Politeknik Pertanian Negeri Pangkajene Kepulauan, 2024)
J Sweet corn (Zea mays saccharata Sturt) is a type of agricultural plant that produces a lot of carbohydrates. The aim of the research is to determine the effect of biosaka concentration, the effect of biosaka time interval, and the interaction between concentration and time interval of biosaka on the growth and production of sweet corn plants. 2 factor factorial design, the first factor is Biosaka concentration (K) which consists of 2 treatment levels, 40 ml/15L and 50ml/15L. the second group is Biosaka Time Interval (W) which consists of 3 treatment levels, once every 3 days, once every 6 days and once every 9 days. The observation parameters are plant height, number of leaves, flowering age, number of seeds per seed, number of rows per row, production per unit. The results showed that the height growth of sweet corn plants with the best average yield was 158.07 cm in the K2W1 treatment, the best average number of leaves was 11.33 in the K2W3 treatment, the average flowering age for the best yield was 50.33 in K1W2 treatment. The best sweet corn production yield was 4.97 in the K2W1 treatment